Evaluation of Microscope Training during the Covid-19 Pandemic - Kazuki, KIHO; Yoshiaki, TAKITANI; Tomoya, HASEGAWA; Chinami, SAKAI; Satoshi, KAWANO; Yuka, MIYAMOTO; Mamoru, WANI; Motohiko, NAGAYAMA; Masatsugu, TOMITA; Hiroki, AKAHORI; Shinpei, TAKEDA; Masashi, TANAKA; et al. (The Japanese Journal of Conservative Dentistry, 2022)
Purpose: Since 2018, the Asahi University School of Dentistry has been holding hands-on training using a microscope (“microscopy training”) for fifth-year students undergoing clinical training at the Department of Endodontics. The introduction of group learning into microscopy training has enabled students to focus as smoothly as instructors. However, the Covid-19 pandemic that began in 2020 resulted in a number of unavoidable lifestyle changes. In the university educational setting, countermeasures had to be introduced to enable lectures to be held for large audiences and to hold practical sessions, and microscopy training for clinical training was no exception. In 2020, the previous group learning format of microscopy training was replaced by individual practical learning at a time specified by the instructor. We compared the effect of this change in method on learning and report the results here. Method: Microscopy training was provided to 42 students who applied to participate. Handouts summarizing the structure and the method of using the microscope were distributed 1 week before the training, and advance study was encouraged. At the beginning of the training session, the time taken to focus at maximum magnification on the orifice of the palatal root canal of a maxillary left first premolar fitted to a model jawbone was measured. The participants then engaged in individual learning with the microscope while referring to the handouts. Next, the instructor provided feedback and performed a demonstration, after which further time was allotted for individual learning. The focus adjustment time was re-measured at the end of the training session, and statistical analysis was conducted using a Mann-Whitney U test with p<0.05 regarded as significant. Results and Discussion: There was no significant difference in the time required to focus at the beginning of the training session between the 2020 and 2019 students, which involved group learning. However, the focus adjustment time at the end of the individual learning in 2020 was significantly longer than that of the group learning implemented in 2019. Although the results of this study did show a significant difference in focus adjustment time, we do not conclude that individual study is inferior. Instead, the results appear to suggest that the effectiveness of individual study is not maximized when it simply replaces group learning, and that further creative adjustments to learning methods are required to fit the context.